Bioconvection due to gyrotactic microbes in a nanofluid flow through a porous medium. Issue 12 (December 2020) - Ahmad, Sohail; Ashraf, Muhammad; Ali, Kashif
Abstract: The addition of gyrotactic microbes in the nanoparticles is essential to embellish the thermal efficiency of many systems such as microbial fuel cells, bacteria powered micro-mixers, micro-volumes like microfluidics devices, enzyme biosensor and chip-shaped microdevices like bio-microsystems. Porous media also plays a pivotal role in augmentation of the thermal efficiency. Our approach in the present work is to offer a novel study of bioconvection due to gyrotactic microbes in a nanofluid flow comprising thermal radiation within a porous media over a nonlinear shrinking/stretching surface. The entire coupled system involving nonlinear equations is tackled by means of Successive over Relaxation technique. The impacts of the involved parameters on the flow, motile microbes diffusion rate, mass and heat transfer rates are examined and shown through diagrams and tables. Comparisons with graphical and tabular data are provided and observed to be in a good agreement. Numerical results evidently point out that the motile microbes parameter and the bioconvection Peclet number elevate the motile microorganisms' density whereas the thermal radiation phenomenon enhances the temperature. Abstract : Nanofluids; Gyrotactic microbes; Bioconvection; Thermal radiation; Porous medium